2020
DOI: 10.3389/fped.2020.00264
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Alveolar Proteinosis Due to Pneumocystis carinii in Type 1 Hyper-IgM Syndrome: A Case Report

Abstract: Background: Pulmonary alveolar proteinosis (PAP) is a rare diffuse lung disease. Reports of rare cases of PAP due to Pneumocystis jirovecii (P. jirovecii) exist in infants with immunodeficiency diseases, but no cases have been reported to date in pediatric patients with type 1 hyper-IgM syndrome (HIGM1). Case Presentation: Herein, we present a case of PAP secondary to P. jirovecii on an infant with HIGM1. He was admitted to our unit because of cough and tachypnea. Lung biopsy confirmed the diagnosis of PAP, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Hence, patients classically have high IgM but low serum levels of IgG and IgA, leading to an increased risk for bacterial infections. Since the CD40/CD40L pathway also mediates co-stimulation between activated CD4 + T cells and CD40-expressing monocytes, macrophages, and dendritic cells, mutations in either CD40L (X-linked) or in CD40 (AR) also lead to opportunistic infections, notably Pjp [ 257 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 ]. Similarly, nuclear factor-kappa-B essential modulator ( NEMO/IKKγ ) [ 311 , 312 , 313 ], inhibitor of kappa light chain gene enhancer in B cells, alpha ( IκBα ) [ 314 ], or nuclear factor kappa-B subunit 1 ( NFKB1 ) [ 315 , 316 ] are involved in CD40/CD40L signaling, and, when mutated, interfere with CD4 + T cell/APC co-stimulation, resulting in HIGM syndrome, for which there are reports of Pjp.…”
Section: Pneumocystismentioning
confidence: 99%
“…Hence, patients classically have high IgM but low serum levels of IgG and IgA, leading to an increased risk for bacterial infections. Since the CD40/CD40L pathway also mediates co-stimulation between activated CD4 + T cells and CD40-expressing monocytes, macrophages, and dendritic cells, mutations in either CD40L (X-linked) or in CD40 (AR) also lead to opportunistic infections, notably Pjp [ 257 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 ]. Similarly, nuclear factor-kappa-B essential modulator ( NEMO/IKKγ ) [ 311 , 312 , 313 ], inhibitor of kappa light chain gene enhancer in B cells, alpha ( IκBα ) [ 314 ], or nuclear factor kappa-B subunit 1 ( NFKB1 ) [ 315 , 316 ] are involved in CD40/CD40L signaling, and, when mutated, interfere with CD4 + T cell/APC co-stimulation, resulting in HIGM syndrome, for which there are reports of Pjp.…”
Section: Pneumocystismentioning
confidence: 99%
“…The present study presents a case with a novel CD40LG ( c.516T > A , p.Tyr172Ter ) truncating mutation, XHIGM, with PAP. Combined with the four previously reported patients [ 6 8 ], the CD40LG mutation XHIGM with PAP was characterized by the early onset of pulmonary infections at approximately the time of infancy (average: 7.75 months old). Most of these patients would experience delays in the diagnosis.…”
Section: Discussionmentioning
confidence: 70%
“…The clinical data of patients with the CD40LG mutated XHIGM with PAP are presented in Table 1 ; Fig. 2 B [ 6 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have suggested that immunodeficiency can induce PAP. However, only two cases of PAP induced by immune deficiency have been reported[ 1 - 3 ], and the remaining studies are almost all review articles. Therefore, more clinical data are needed to prove the correlation between PAP and immunodeficiency.…”
Section: Introductionmentioning
confidence: 99%